Penguatan Tata Kelola Keuangan Daerah Berbasis Pengelolaan Aset dan Sistem Akuntansi Keuangan pada Kantor Badan Keuangan dan Aset Daerah Kabupaten Situbondo - Misnaini Misnaini; Edi Subiyantoro; Maxion Sumtaky (Journal of Regional Economics Indonesia, 2023)
This study aims to examine the effect of asset management and financial accounting systems on the quality of regional financial reports. This research is a descriptive quantitative approach that tests the hypothesis: the effect of asset management on the quality of regional financial reports and the influence of the financial accounting systems on the quality of regional financial reports. The data used are primary data collected through direct questionnaire surveys. This study used a sample of 35 respondents who were employees of the Situbondo Regency Regional Finance and Asset Office. Data analysis using multiple linear regression analysis. The results of the study show that asset management has a positive effect on the quality of regional financial reports and the financial accounting system has a positive effect on the quality of regional financial reports.